Increased Stiffness Inhibits Invadopodia Formation and Cell Migration in 3D - Chang, Julie; Pang, Emily M.; Adebowale, Kolade; Wisdom, Katrina M.; Chaudhuri, Ovijit (Biophysical journal, 2020)
Cancer cells typically invade through basement membranes (BMs) at key points during metastasis, including primary tumor invasion, intravasation, and extravasation. Cells extend invadopodia protrusions to create channels in the nanoporous BM through which they can invade, either via proteolytic degradation or mechanical force. Increased matrix stiffness can promote cancer progression, and two-dimensional (2D) culture studies indicate that increased stiffness promotes invadopodia degradation activity. However, invadopodia can function mechanically, independent of their degradative activity, and cells do not form fully matured invadopodia or migrate in the direction of the invadopodia in 2D environments. Here, we elucidated the impact of matrix stiffness on the mechanical mode of invadopodia activity of cancer cells cultured in three-dimensional BM-like matrices. Invadopodia formation and cell migration assays were performed for invasive breast cancer cells cultured in mechanically plastic, nanoporous, and minimally degradable interpenetrating networks of reconstituted BM matrix and alginate, which presented a range of elastic moduli from 0.4 to 9.3 kPa. Across this entire range of stiffness, we find that cells form mature invadopodia that often precede migration in the direction of the protrusion. However, at higher stiffness, cells form shorter and more transient invadopodia and are less likely to extend invadopodia overall, contrasting with results from 2D studies. Subsequently, cell migration is diminished in stiff environments. Thus, although previous studies indicate that increased stiffness may promote malignant phenotypes and the degradative activity of invadopodia, our findings show that increased stiffness physically restricts invadopodia extension and cell migration in three-dimensional, BM-like environments.